Anakinra Therapy for Non-cancer Inflammatory Diseases - Cavalli, Giulio; Dinarello, Charles A. (Frontiers in Pharmacology, 2018)
Interleukin-1 (IL-1) is the prototypic inflammatory cytokine: two distinct ligands (IL-1α and IL-1β) bind the IL-1 type 1 receptor (IL-1R1) and induce a myriad of secondary inflammatory mediators, including prostaglandins, cytokines and chemokines. IL-1α is constitutively present in endothelial and epithelial cells whereas IL-1β is inducible in myeloid cells and released following cleavage by caspase 1. Over the past 30 years, IL-1-mediated inflammation has been established in a broad spectrum of diseases, ranging from rare autoinflammatory diseases to common conditions such as gout and rheumatoid arthritis, type 2 diabetes, atherosclerosis, and acute myocardial infarction. Blocking IL 1 entered the clinical arena with anakinra, the recombinant form of the naturally occurring IL 1 Receptor antagonist (IL 1Ra); IL 1Ra prevents the binding of IL 1α as well as IL 1β to IL 1R1. Quenching IL 1-mediated inflammation prevents the detrimental consequences of tissue damage and organ dysfunction. Although anakinra is presently approved for the treatment of rheumatoid arthritis and cryopyrin-associated periodic syndromes, off-label use of anakinra far exceeds its approved indications. Dosing of 100 mg of anakinra subcutaneously provides clinically evident benefits within days and for some diseases, anakinra has been used daily for over 12 years. Compared to other biologics, anakinra has an unparalleled record of safety and opportunistic infections, particularly Mycobacterium tuberculosis are rare, even in populations at risk for reactivation of latent infections. Because of this excellent safety profile and relative short duration of action, anakinra can also be used as a diagnostic tool for undefined diseases mediated by IL 1. Although anakinra is presently in clinical trials to treat cancer, this review focuses on anakinra treatment of acute as well as chronic inflammatory diseases.